Incretins and SGLT-2i Therapy of Type 2 Diabetes – Real Life Study of Their Therapeutic and Economic Effects - Mitkova, Zornitsa; Mitov, Konstantin; Valov, Vasil; Manova, Manoela; Savova, Alexandra; Kamusheva, Maria; Tcharaktchiev, Dimitar; Angelov, Zhivko; Angelova, Galia; Petrova, Guenka (Frontiers in Pharmacology, 2019)
Aims: Incretin’s (DPP-4i and GLP-1 RA) and SGLT-2i groups are now routinely used for type 2 diabetes therapy and comprise a large number of medicinal products. The long term therapeutic and economic effect of the incretins’ and SGLT-2i in real life setting is not well documented. The goal of the current study is to analyze the cost and results of incretins’ and SGLT-2i based therapy for type 2 diabetes in Bulgaria. Methods: The study is using an information about the changes in the HbA1c level from the National diabetes register for 6122 patients and cost paid by the National health insurance fund (NHIF) for diabetes complication, and medicines prices. Results: The results show that after the therapy patients achieved excellent diabetes control. There were no HbA1c values less than 6% before treatment. After the therapy, 3356 people showed values less than 7% HbA1c. It is considered as very good diabetic control. The number of people with HbA1c above 8% is decreasing significantly. Number of people with values above 9% is decreasing almost 4 times. HbA1c level decreases with the highest percentage for the patients treated with GLP-1 RA, followed by those treated with DPP-4i and SGLT-2i. For a year NHIF reimbursed 5.25 million of BGN for incretins’ and SGLT-2i therapy. NHIF can save between BGN 306 and 510 thousand from incidents that have not occurred as a result of 5 years of therapy. Conclusions: Incretins’ and SGLT-2i therapy steadily decrease the HbA1c level and risk of developing the diabetic incidents is reduced between 333 to 465 cases among 6122 treated patients. Avoided cost for therapy of diabetes incidents account for 305 and 510 thousands of BGN.